Perbandingan Hasil Nilai Baca Konsumsi Air Antara Sensor Water flow YF-B6 dan YF-S201 dalam Penggunaan Internet of Things - Kurnia Bakti, Very; Rais, Rais; Basit, Abdul; Nugroho, Wildani Eko; Nishom, M. (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
The use of clean water is very necessary for human life, the existence of clean water requires adequate infrastructure, especially in the distribution and quality of the water. Water usage measurements at PDAM and Pamsimas still use analog water meters, although the reading values are relatively accurate, the entire calculation process is less efficient because it has to be done manually by humans which requires energy and time and there is the possibility of recording errors. Water flow sensors are able to provide an alternative as a projection for the future which makes it possible to build smart water meters by applying IoT. However, the level of accuracy of water flow sensor readings needs to be studied more deeply for its use considering the many types of shapes, materials and sizes of water flow sensors. This research presents a comparison of sensor reading values by changing several constant parameters in each test, which is the most precise and accurate in each measurement test. These results are up to the accumulated amount of water in milli liters, then measured to obtain the accuracy value of each sensor reading value, thus the comparison of two water flow sensors can be used as a reference for the use of which sensor is most suitable for use as a water meter for each different uses.